Kehendak Buta Perspektif Schopenhauer - I Nyoman Surpa Adisastra; i Putu Sinta Oktaviani; Luh Kartika Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
, Arthur Schopenhauer was a German philosopher who continued the post-Kant tradition of philosophy. Kant's thoughts emerge in Schopenhauer's view of the world as ideas and wills. Kant stated that human knowledge is limited to the realm of appearances or phenomena, so that things in him (das Ding an sich) can never be known to humans. The thought of the world as I want it to be, life is full of suffering, and it would be so much better if it wasn't born. Some people seem pessimistic, including Arthur Schopenhauer.